Discrepancies between FDA documents and ClinicalTrials.gov for Orphan Drug-related clinical trial data - Mohua Chakraborty Choudhury; Indraneel Chakraborty; Gayatri Saberwal (Public Library of Science (PLoS), 2022)
Clinical trial registries such as ClinicalTrials.gov (CTG) hold large amounts of data regarding trials. Drugs for rare diseases are known as orphan drugs (ODs), and it is particularly important that trials for ODs are registered, and the data in the trial record are accurate. However, there may be discrepancies between trial-related data that were the basis for the approval of a drug, as available from Food and Drug Administration (FDA) documents such as the Medical Review, and the data in CTG. We performed an audit of FDA-approved ODs, comparing trial-related data on phase, enrollment, and enrollment attribute (anticipated or actual) in such FDA documents and in CTG. The Medical Reviews of 63 ODs listed 422 trials. We used study identifiers in the Medical Reviews to find matches with the trial ID number, 'Other ID' or 'Acronyms' in CTG, and identified 202 trials that were registered with CTG. In comparing the phase data from the 'Table of Clinical Studies' of the Medical Review, with the data in CTG, there were exact matches in only 75% of the cases. The enrollment matched only in 70% of the cases, and the enrollment attribute in 91% of the cases. A similar trend was found for the sub-set of pivotal trials. Going forward, for all trials listed in a registry, it is important to provide the trial ID in the Medical Review. This will ensure that all trials that are the basis of a drug approval can be swiftly and unambiguously identified in CTG. Also, there continue to be discrepancies in trial data between FDA documents and CTG. Data in the trial records in CTG need to be updated when relevant.